High on drugs: Multi-institutional pilot study examining the effects of substance use on acute pain management. Issue 5 (May 2019) - Salottolo, Kristin; Peck, Laura; Carrick, Matthew; Tanner, Allen; Madayag, Robert; McGuire, Emmett; Bar-Or, David
Highlights: These results demonstrate significantly greater opioid consumption in patients testing positive for drugs, compared to patients with a negative urine drug screen. Overall, drug users have a 1.4-fold increased consumption of opioids for acute pain vs. non-users. These preliminary data suggest that substance use preceding injury results in greater consumption of opioids, particularly when opiates are detected. Abstract: Introduction: Substance use and abuse may have the significant, but unanticipated, consequence of lessening the efficacy of opioid analgesics for acute pain management. We hypothesized that pre-injury substance use increases opioid analgesic consumption following traumatic injury. Methods: This retrospective multi-institutional pilot study included admitted patients to four level 1 trauma centers with vehicular trauma over four months (n = 176). We examined the effect of positive urine drug screen (UDS; 7-drug panel, examined individually and combined, yes/no) and positive blood alcohol content (BAC, ≥80 mg/dL) on pain management with opioid analgesics over the hospital stay. Average daily opioid consumption was examined using a repeated measures mixed model, by positive UDS and BAC findings, adjusting for age, injury severity score, and non-opioid analgesia. Opioid analgesics were converted to milligram morphine equivalents (MME) and analyzed with a square-root transformation due to non-normality. Results: A positive drug or alcohol test was reported in 33.5% (59/176), including 12.5% (n = 22) with positive UDS and 26% (n = 45) with a positive BAC. There were no differences in gender, injury severity scores, Glasgow coma scores, or cause of vehicular trauma between substance users and non-users; only age was significantly different. Patients with a positive UDS consumed significantly more opioids compared to those with a negative UDS (34.7 MME vs. 24.7 MME, p = 0.04), after adjustment. Individually, detection of opiates, THC, cocaine, and amphetamines were associated with increased opioid consumption compared to their UDS negative counterparts; on the other hand, benzodiazepines and alcohol intoxication were associated with reduced opioid consumption during the course of hospitalization. However, none of the individual UDS results reached statistical significance. The largest effect of all the individual drugs was with opiates, which was associated with a borderline significant increase in opioid analgesic consumption (p = 0.06). Conclusions: Our preliminary data suggest drug use may significantly alter acute pain management following traumatic injury, corresponding to 40% increase in opioid analgesia for substance users than non-users. These results may have broad reaching implications because of the high prevalence of substance use in the trauma population.